Enhanced Solar Hydrogen Generation by a Heterojunction of Perovskite‐type La2Ti2O7 Nanosheets Doped with CdS Quantum Dots. Issue 11 (23rd August 2016) - Hu, Sujuan; Zhu, Mingshan
Abstract: A heterojunction of a perovskite‐type La2 Ti2 O7 (LTO)/CdS quantum dot (QD) nanocomposite was prepared by the chemical bath deposition method. The solar‐light‐driven H2 generation results show that this CdS QDs/LTO heterojunction exhibits great improvement in the photocatalytic H2 production and its photoelectrochemical properties in comparison with pure CdS QDs and LTO nanosheets. A possible enhanced mechanism of photoinduced interfacial charge transfer between CdS and LTO is proposed for the heterojunction. The shift of the CdS conduction band (CB) edge can enlarge the CB potential difference between CdS QDs and LTO, enhancing transferred driven force of the interfacial electrons and finally improving the two components' separation activity of photogenerated carriers. This study provides a promising method for constructing an efficient photoinduced interfacial charge transfer over LTO and CdS QD heterojunctions for photocatalytic hydrogen production. Abstract : Heterojunction for hydrogen economy : A heterojunction of perovskite‐type La2 Ti2 O7 and CdS quantum dots was designed to enhance solar‐light‐driven H2 generation owing to the efficient interfacial charge transfer.